Growth and osmoregulation in Salmo salar L. juveniles 1+, 1½ + and 2+ reared under restrained salinity - José Fernando Magalhães Gonçalves; Stela Carraça; Alfredo Damasceno-Oliveira; Córalia Vicente; Paulo Martins da Costa; Manuel Lopes-Lima; Rodrigo Otávio de Almeida Ozório (Scientia Agricola, 2013)
The freshwater phase of Atlantic salmon Salmo salar L vary between one and eight years. The reduction of the freshwater phase is desirable to reduce freshwater usage, human resources and to increase year round availability of pan-sized salmon. Three trials were conducted to investigate the possibility of supply the market in a year-round basis, with pan-sized Atlantic salmon Salmo salar L. (250-300 g) in Portugal (southern limit of the natural distribution of this species). This study primarily aimed to compare the osmoregulatory ability and growth of different fish sizes, smolts 1+ (trial 1), 1.5+ (trial 2) and 2+ (trial 3), in freshwater and seawater conditions. Additionally, effects of photoperiod were determined in smolts 1.5+ (trial 2) for both freshwater and seawater groups. The increments in the plasma osmolality and chlorine concentrations after seawater transfer suggest an identical development in the hypo-osmoregulation capacity among the different age classes. In all trials, weight gain was smaller after 30 d of saltwater transfer when compared to fish reared in freshwater. However, the growth depression was temporary. Seawater group showed a compensatory growth in the immediate months, which permitted an improvement in growth rates. At the end of trials there were minor differences on growth performance between freshwater and seawater groups. Specific growth rates varied between 0.7 and 1.0 % day-1, according to the age and /or size and transfer season.